Cornea stress test--evaluation of corneal endothelial function in vivo by contact lens induced stress - Saini Jagjit; Mittal Sangeet; Anand Mrinal (Indian Journal of Ophthalmology, 1997)
Reliable and valid assessment of corneal endothelial function is a critical input for diagnosing, prognosticating and monitoring progression of disorders affecting corneal endothelium. In 123 eyes, corneal endothelial function was assessed employing data from the corneal hydration recovery dynamics. Serial pachometric readings were recorded on Haag-Striet pachometer with Mishima-Hedbys modification before and after two hours of thick soft contact lens wear. Percentage Recovery Per Hour (PRPH) was derived from raw data as an index of endothelial function. Assessed PRPH in pseudophakic corneal oedema and Fuchs′ endothelial dystrophy eyes (35.9 +/- 9.8%) was significantly lower than normal controls (61.9 +/- 10.5%). On employing receiver operation characteristics curve analysis the tested results demonstrated high sensitivity (87%) and specificity (92%) for detection of low endothelial function at PRPH cut off of 47.5%. Using this PRPH cut off, 80% of Fuchs′ endothelial dystrophy and 93.3% of pseudophakic corneal oedema eyes could be demonstrated to have low endothelial function. A total of 66.7% of diabetic eyes also demonstrated PRPH of lower than 47.5%. Clear corneal grafts demonstrated PRPH values of 24.6% to 73.0%. Of 6 corneal grafts that demonstrated initial PRPH of lower than 47.5%, 4 failed within 4 to 6 months. Our data demonstrated high sensitivity and specificity of this corneal stress test. PRPH index was useful in quantifying endothelial function in clinical disorders including diabetes mellitus. The index PRPH was demonstrated to be useful in monitoring and prognosticating outcome of corneal grafts.